Capital Account Liberalization and the Real Exchange Rate in Chile. (IMF Working Papers; Working Paper ;, 2005)
After the failure of the early 1980s, a second attempt at capital account liberalization was gradually carried out in Chile during the 1990s, this time in parallel with increased exchange rate flexibility. Capital account regulations were applied to support the independent monetary policy committed to the inflation target, while the exchange rate was quasi-pegged within a band that targeted the real exchange rate (RER). Still, the policy framework directed at stabilizing the RER appears to have been of limited effectiveness, with the surges and sudden-stops in capital flows playing an important role in RER dynamics. Foreign exchange market intervention appears not to have affected the RER while reserve requirement appears to have exerted a depreciating effect. Government spending and import tariffs, appear to be significant tools to moderate the real appreciation thus providing one additional reason for adopting a countercyclical fiscal policy and accelerating trade openness.